Pengaruh Motivasi dan Penerapan Metode Pembelajaran Kooperatif Terhadap Prestasi Belajar Mahasiswa Pendidikan Ekonomi di Universitas PGRI Wiranegara - Aris Maiyanti; Sugeng Pradikto (Institut Nalanda, 2025)
This research aims to examine the influence of motivation and the application of cooperative learning methods on the learning achievement of students in the economic education study program at PGRI Wiranegara University. The research approach used is quantitative involving students as respondents. Data analysis was carried out using validity, reliability and significance tests. The research results show that motivation and cooperative learning methods have a significant influence on student learning achievement. The validity test produces a significance value of more than 0.05 which shows that all variables are valid and interconnected. Apart from that, the reliability test produced a value of more than 0.600 so that all variables were declared reliable. Student motivation contributes greatly to increasing their activeness and involvement during learning, while cooperative learning methods have proven effective in improving collaboration, critical thinking and problem solving abilities. This research recommends the application of cooperative learning methods that are tailored to students' needs to encourage the development of their academic achievement and social skills.